Advanced single-phase non-isolated microinverter with time-sharing maximum power point tracking control strategy - Alhasi, Anees; Luk, Patrick Chi-Kwong; Ibrahim, Khalifa Aliyu; Luo, Zhenhua (MDPI, 2025)
Partial shading poses a significant challenge to photovoltaic (PV) systems by degrading power output and overall efficiency, especially under non-uniform irradiance conditions. This paper proposes an advanced time-sharing maximum power point tracking (MPPT) control strategy implemented through a non-isolated single-phase multi-input microinverter architecture. The system enables individual power regulation for multiple PV modules while preserving their voltage–current (V–I) characteristics and eliminating the need for additional active switches. Building on the concept of distributed MPPT (DMPPT), a flexible full power processing (FPP) framework is introduced, wherein a single MPPT controller sequentially optimizes each module’s output. By leveraging the slow-varying nature of PV characteristics, the proposed algorithm updates control parameters every half-cycle of the AC output, significantly enhancing controller utilization and reducing system complexity and cost. The control strategy is validated through detailed simulations and experimental testing under dynamic partial shading scenarios. Results confirm that the proposed system maximizes power extraction, maintains voltage stability, and offers improved thermal performance, particularly through the integration of GaN power devices. Overall, the method presents a robust, cost-effective, and scalable solution for next-generation PV systems operating in variable environmental conditions.
This article belongs to the Special Issue Advanced Control Strategies for Photovoltaic Energy Systems
Keywords: 40 Engineering; 4008 Electrical Engineering; 4009 Electronics, Sensors and Digital Hardware; 7 Affordable and Clean Energy; 33 Built environment and design; 51 Physical sciences; microinverter; efficiency; distributed maximum power tracking (DMPPT); mismatched photovoltaic (PV); full power processing (FPP); time-sharing MPPT control strategy